Audiowizualne oblicza przesądu. O niektórych funkcjach motywu lustra w dziele filmowym - Kuc, Agnieszka (Załącznik Kulturoznawczy, 2023)
The purpose of this article is to show the role played by the mirrors and related to them themes in audiovisual works, not only at the production stage, but also as symbols which are hidden in those works. I presented, in an abbreviation, how the filmmakers are using the mirrors in the production process, i.e. technical aspects, as well as their functions in the frame, like including them as an attractive ornament to the scene. Each role and function of the mirror has been highlighted in the article by examples from the selected movies. In the next part I focused on showing the mirror from the perspective of superstitions that are associated with it, and I also made an attempt to isolate and clarify its roles and functions which can be found in the movies. The division I proposed was constructed in such a way that it could be easily explained, in one or two words, what lies beneath them, and so the distribution is as follows: wraith (emphasis on the problem of identity), magical mirror (introducing elements of magic to the movies), the gates of truth (revealing the true face of reality), medium (mediating between the worlds), bad omen (the preaching of someone’s death), prison for the soul.